Resilience: supporting children’s self-regulation in infant and toddler classrooms - Horm, Diane M.; Jeon, Shinyoung; Ruvalcaba, Denise Vega; Castle, Sherri (Frontiers in Psychology, 2024)
Resilience is a process that develops as a complex transaction as children experience and shape their contexts. Self-regulation is an aspect of resilience that has received increased attention as a key mechanism predicting a variety of important short-and long-term outcomes. The current study examined how the self-regulation skills of infants and toddlers in a classroom could potentially shape classroom interactions and quality which, in turn, could potentially shape the development of self-regulation skills of the individual infants and toddlers enrolled in the classroom across an early childhood program year. The unique contribution of this study is the focus on a critical component of resilience, self-regulation, in an understudied age group, infants and toddlers, in an important and understudied context, the infant-toddler early childhood classroom. Methods: Data are from a statewide evaluation of early childhood programs serving children birth to age 3 growing up in low-income contexts. Multi-level mediation models were employed. We found a significant indirect path. The results showed that classroom-level average self-regulation skills demonstrated by infants and toddlers in the fall predicted higher levels of teachers' implementation of three important aspects of classroom quality. We also found that higher levels of teachers' support for social-emotional, cognitive, and language development associated with children's increased growth in self-regulation skills from fall to spring. The direct path from classroom-level self-regulation demonstrated in the fall to individual children's gain in self-regulation was not significant. Discussion: These findings, unique due to the focus on infants and toddlers in a classroom context, are discussed within the larger body of existing self-regulation research conducted with older children and prevalent theories. Implications for both infant-toddler classroom practices and future research are addressed. Relative to practice, our findings have implications for informing how the development of self-regulation, an important component of resilience, can be supported in the youngest children, infants and toddlers, specifically those enrolled in center-based classrooms serving young children growing up in families with low incomes. Future research using different measures, designs, analytical strategies, and diverse samples and contexts is needed to further explain very young children's development of self-regulation, a critical component of resilience.